TEACHING WRITING IN ENGLISH - Jomurzayeva Odinaxon Dilshodjon qizi; Ahmedova Matluba Ibragimjonovna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation: Writing is a complex communicative activity. It helps to communicate in the written form with the help of graphical symbols. Writing is a type of speech activity as «a communicative skill to encode, store and send messages with the help of written symbols». The product of this type of speech activity is a text for reading.